Strategi Komunikasi Pemasaran Polca Coffee dalam Meningkatkan Brand Awareness Melalui Media Instagram - Agistian, Virgiawan; Meliala, Robbikal Muntaha; Bender, George Wilhelm (Universitas Pahlawan Tuanku Tambusai, 2025)
The advancement of digital technology not only simplifies daily life but also directly influences how companies approach consumers in the marketing world. The presence of social media has become a primary tool used by companies to interact with consumers, increase brand exposure, and build customer loyalty. Marketing communication is a strategic step that must be undertaken by companies or brands to deliver messages focused on enhancing brand awareness and consumer engagement. Instagram, as one of the most popular social media platforms, facilitates brands in presenting visually appealing content that invites active consumer participation. A qualitative approach has been used as the method in this research. Descriptive data regarding individuals and observed behaviors, both in written and oral forms, were obtained through this approach. In this study, the results of interviews analyzed with respondents indicate that the marketing communication strategy implemented by Polca Coffee has been systematically designed using the SOSTAC framework and a brand awareness approach. Based on the research conducted on Polca Coffee's marketing communication strategy to increase brand awareness through Instagram, several conclusions can be drawn as follows: 1. The marketing strategy implemented by Polca Coffee has been systematically designed using the SOSTAC framework, which includes situation analysis, goal setting, strategy development, tactical application, actions, and controls. 2. Polca Coffee has successfully increased brand awareness by optimizing the use of social media through attractive visual content, relevant storytelling, and the utilization of Instagram features.